2019
DOI: 10.3390/app9163239
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-Based Sentiment Analysis Using Aspect Map

Abstract: Aspect-based sentiment analysis (ABSA) is the task of classifying the sentiment of a specific aspect in a text. Because a single text usually has multiple aspects which are expressed independently, ABSA is a crucial task for in-depth opinion mining. A key point of solving ABSA is to align sentiment expressions with their proper target aspect in a text. Thus, many recent neural models have applied attention mechanisms to learning the alignment. However, it is problematic to depend solely on attention mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Knowledge-base for entity recognition and linking was constructed on official data, including fields of studies, study programs and universities and their colloquialisms in social media. NER rule-based matcher was implemented using spaCy 7…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge-base for entity recognition and linking was constructed on official data, including fields of studies, study programs and universities and their colloquialisms in social media. NER rule-based matcher was implemented using spaCy 7…”
Section: Methodsmentioning
confidence: 99%
“…Different architectures are considered, especially neural sequential models, such as long short-term memory (LSTM) networks with different modifications -hierarchical attention mechanism [4,5], delayed memory update [6]. Another approach suggests convolutional neural network based (CNN-based) aspect-level sentiment classification models, consisting of two CNNs [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, all these methods lack of semantic logicality and fluency for context divided by aspect-specific, hence the representation of context is continuous so that the semantic information is not fluent. Yunseok Noh (Noh et al 2019) applied CNN as Aspect-Map Extraction Network (AMEN) to extract the representation of aspect to constitute an aspect map, then regarded the representations of aspect and context as input to conduct sentiment classification. Attention over Attention mechanism was introduced to model the interactive relationships between aspect-specific and every word of text, which can assign the greater weights to some important words on sentiment classification (Huang et al 2018).…”
Section: Aspect-level Sentiment Classificationmentioning
confidence: 99%
“…Udit et al [14] developed an improved sentiment analysis method using image processing techniques based on visual data. Other research related to aspect-based sentiment analysis (ABSA) classify the sentiment of a specific aspect in a text presented in [15][16][17]. Earlier research has shown that these approaches are appropriate only under certain conditions.…”
Section: Computer Vision and Image Processing Approaches For Sentiment Analysismentioning
confidence: 99%